Staphylococcal chromosomal cassettes mec (SCCmec): A mobile genetic element in methicillin-resistant Staphylococcus aureus. (December 2016) - Liu, Junyan; Chen, Dingqiang; Peters, Brian M.; Li, Lin; Li, Bing; Xu, Zhenbo; Shirliff, Mark E.
Abstract: Considered to be a potential "superbug", methicillin-resistant Staphylococcus aureus (MRSA) has been one of the major recent infectious pathogens and thus poses a challenge to hospital infection control. The mobile genetic element staphylococcal chromosomal cassette mec (SCC mec ) carries both the mecA or mecC gene, encoding for a novel speciﬁc penicillin-binding protein (PBP2a), and site-speciﬁc recombinase genes ccrAB or/and ccrC . In MRSA, the acquisition of SCC mec leads to the resistance to the β-lactam antibiotics. As SCC mec plays a core role in the antimicrobial resistance characteristics, molecular epidemiology and evolution of MRSA, a thorough summary and comprehensive understanding of the prevalence and structural characteristics of SCC mec may aid in global surveillance, implementation and investigation on MRSA isolates, as well as further development of preventive and therapeutic approaches. Consequently, this review is aimed at describing the history, prevalence, types and subtypes, and current typing methods of SCC mec, with the focus on the typical structures of the SCC mec cassette. Highlights: MRSA has been one of the major recent infectious pathogens and thus poses a challenge to hospital infection control. SCC mec plays a core role in the antimicrobial resistance characteristics, molecular epidemiology and evolution of MRSA. The history of MRSA, SCC mec types and subtypes were summarized and the prevalence of SCC mec types were illustrated. The typical genetic structures of type I to XI SCC mec and their subtypes were described and illustrated elaborately. SCC mec typing methods including multiplex PCR strategy, target DNA microarray and whole genome sequencing were reviewed.